Work Attitudes Among Office Personnel at MSU-Iligan Institute of Technology, Iligan City Philippines - Codilla, Katrina Lumayag; Quinal, Jalil Evangelista (Universitas Muhammadiyah Yogyakarta, 2019)
The skills, competencies, and attitudes of employees determine the success or failure of any organization. The attainment of the objectives of an organization is determined in terms of profit or advancement of status. Thus, when employees do not perform well, the productivity of the organization suffers.This is a correlation study which explores the work attitude of employees using the variables such as generation, length of service, academic achievement, and employment status. A work attitude questionnaire (α=0.856) composed of statements relating to the manifestation and consideration of attitudes, habits, and behaviors was utilized. A total of 147 participants were determined using the purposive-convenient sampling procedure.Major findings include that female millennials as the foremost office personnel in the Institute. Majority are permanent employees with college degrees and have been working for more than ten years. The work attitude of the participants was excellent for Generation X participants, Master’s degree holder, employed as casuals, and those who have been working for more than five years. There is a significant relationship which was found between the participants’ work attitude and the variables generation, academic achievement, length of service, and status of employment.With these findings, it is then deduced that the work attitude of the employees is affected with their status of employment, generation, academic achievement, and length of service. Thus it is recommended that office personnel must pursue higher education and the management should provide avenue for their scholastic development. It is also recommended that further studies be undertaken to explore work attitudes alongside the performance of the participants such as punctuality and output.